1999
DOI: 10.1016/s0014-5793(99)00641-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against the regulation of caldesmon inhibitory activity by p42/p44erk mitogen‐activated protein kinase in vitro and demonstration of another caldesmon kinase in intact gizzard smooth muscle

Abstract: The effect of direct phosphorylation by recombinant p44 erk1 mitogen-activated protein kinase on the inhibitory activity of caldesmon and its C-terminal fragment H1 was studied in vitro. Neither inhibition of actin-tropomyosin activated ATPase of heavy meromyosin by caldesmon or H1, nor inhibition of the actin-tropomyosin motility over heavy meromyosin by H1 was significantly affected by the phosphorylation while only a moderate effect on the actin-activated component of heavy meromyosin ATPase inhibition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Despite inhibition of ERK 1/2 activation by U0126 treatment, partial caldesmon phosphorylation still occurred. Consistent with these findings, others have shown that inhibition of MEK signalling reduces but does not abolish caldesmon phosphorylation [37, 38]. In addition, U0126 at the higher concentrations showed a disproportionate increase in FFIR in relation to the more modest decrease in caldesmon phosphorylation.…”
Section: Discussionsupporting
confidence: 72%
“…Despite inhibition of ERK 1/2 activation by U0126 treatment, partial caldesmon phosphorylation still occurred. Consistent with these findings, others have shown that inhibition of MEK signalling reduces but does not abolish caldesmon phosphorylation [37, 38]. In addition, U0126 at the higher concentrations showed a disproportionate increase in FFIR in relation to the more modest decrease in caldesmon phosphorylation.…”
Section: Discussionsupporting
confidence: 72%
“…Adam and Hathaway (1) have presented compelling evidence to suggest that the p42/p44 mitogen-activated protein (MAP) kinases could account for ϳ40% of stimulation-induced increases in caldesmon phosphorylation. Consistent with these findings, we and others (13,25) have shown that inhibition of cellular MAP kinase activity decreases but does not abolish caldesmon phosphorylation.Therefore, what is the identity of the other kinases that are potentially important in the regulation of a smooth muscle contraction? In addition to the potential role for MAP kinase activity (1, 5, 11) the other kinases that have been proposed to phosphorylate caldesmon include Ca 2ϩ /calmodulin-dependent protein kinase II (CaM kinase II), (21), protein kinase C (PKC), (20, 47), cdc42 kinase (30), and casein kinase 2 (CK2) (2,45,51).…”
supporting
confidence: 92%
“…Adam and Hathaway (1) have presented compelling evidence to suggest that the p42/p44 mitogen-activated protein (MAP) kinases could account for ϳ40% of stimulation-induced increases in caldesmon phosphorylation. Consistent with these findings, we and others (13,25) have shown that inhibition of cellular MAP kinase activity decreases but does not abolish caldesmon phosphorylation.…”
supporting
confidence: 92%
“…In vascular smooth muscle, ERK has been demonstrated to be a physiologically relevant caldesmon kinase that phosphorylates caldesmon at Ser 789 (1,2). However, whether caldesmon phosphorylation at ERK-specific sites induces smooth muscle contraction remains controversial (10,24,32). Our recent studies with uterine arteries of pregnant sheep suggest that ERK-mediated phosphorylation of caldesmon may stabilize the inhibitory effect of caldesmon on actin-activated myosin ATPase (49).…”
Section: Phenylephrine-induced [Ca 2ϩ ] I and Tension Phenylephrinementioning
confidence: 99%